Evaluation of TNF-α and TNF-R1 immunomarkers in Renal Failure Patients in Karbala province - Mezher, Z. Abdul Alamir (Technium BioChemMed, 2024)
Renal failure is characterized by height level of pro-inflammatory cytokines, mainly Tumor necrosis factor-alpha (TNF-α) and its receptor TNF-R1. The aim was to investigate the association of TNF-α and TNF-R1 levels in Renal Failure.This study was carried out from February 2022 to March 2023 in the labs of Thi-Qar University's Col1ege of Education for Pure Sciences. In partnership with Al-Hussein Teaching Hospital, Nasiriyah General Hospital, and Thi-Qar Center for Nephrology and Dialysis in Thi-Qar Province .The study comprised (100) patients for both sex : (40 patients with diabetes mellitus), (40 patients without diabetes mellitus) whose serum urea level and serum creatinine level were examined, and (40 healthy).The level of biochemical indicators were measured, which included urea, creatinine, albumin and total protein where the study discovered a considerable rise in urea and creatinine levels compared to healthy subjects and standard rates, and this increase is related 'with a decrease GFR', while there is decrease in rate of albumin and total protein. The statistical analysis' findings revealed a considerable difference (p <0.05) in patients with RF in concentration of the TNF-α and TNF-R1, where they were examined for 80 samples of RF patients, and 40 healthy samples in the control group. The number of RF patients in Thi-Qar province showed a marked increase in the yearly rate of hemodialysis. A third of all patients had a considerable prevalence of RF linked to hypertension. The study concluded that a significant effect of TNF-α is associated with markers of kidney disease severity and distant organ dysfunction among patients with RF. In addition, this study found a correlation between the effects of TNF- α on end-stage renal disease. Extensive studies are needed to confirm these relationships.